PENGARUH KEPEMIMPINAN DAN KOMPENSASI TERHADAP TURNOVER INTENTION PERAWAT RSIA ERIA BUNDA PEKANBARU DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - F. Panjaitan Christovel; Hendriani Susi; Pramadewi Arwinence (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
Every organization or company carries out various policies in overcomingvarious problems within the organization. One of the problems that is often faced is thelarge number of human resources who have the intention or think to leave theorganization. Factors that influence this include leadership, compensation policy,promotion, work environment and job satisfaction. So, with these indications, the authorschose to conduct research in one of the hospitals, namely RSIA Eria Bunda Pekanbaruwith a focus on leadership issues, compensation which has an impact on nurses' turnoverintention. RSIA Eria Bunda is one of the hospitals in the Pekanbaru area with 78 nurses.The respondents are all nurses with the analytical method used is path analysis. Theresults show that leadership and compensation have a significant effect on nurses'turnover intention with job satisfaction as an intervening variable at RSIA Eria Bunda. Keywords: Turnover Intention, Leadership, Compensation, Job Satisfaction